AN ASSESSMENT OF ADHERENCE FOR INSULIN USE IN PATIENTS WITH DIABETES - Pitak, Panitan; Neelapaijit, Nipaporn; Fuangchan, Anjana; Dhippayom, Teerapon (Thai Bulletin of Pharmaceutical Sciences, 2023)
Evaluating patients’ adherence to their prescriptions is important when considering plans between patients and health care workers, and in explaining whether the desired outcomes of the plans are achieved. This article is intended to compile a variety of definitions pertaining to medication adherence and to consider the advantages and disadvantages of the assessment tools used to evaluate the adherence of patients with type 1 and type 2 diabetes to their prescriptions. It also aims to explain the association between different levels of insulin adherence, based on various assessment tools, and diabetes control. Generally, medication adherence measures are divided into 2 types, i.e. whether they use direct methods or indirect methods to measure medication taking behavior. Some tools were developed specifically for a particular group of medicines. At present, certain adherence measuring tools for general medicine are applied for measuring insulin adherence. However, there is one tool that has been specifically developed to measure insulin adherence, i.e. Morisky Insulin Adherence Scale (MIAS). The current evidence suggests that the association between adherence and blood glucose control is varied and influenced by the adherence tool being used. Currently, there is no standard tool for assessing adherence to insulin injections. In addition, the correct use of insulin has not been incorporated as part of the assessment of adherence to insulin injections. Selecting an appropriate adherence tool should consider patient characteristics, including age and co-morbidity; the correct use of insulin; and other factors that may affect adherence. Furthermore, an assessment of adherence to insulin should not be derived only from a single tool since each tool has different potential advantages and limitations in providing an accurate figure of adherence.